First record of Derogenes varicus and Dinurus scombri (Digenea: Hemiurata) from Red Sea fishes, Yemen - Al-Zubaidy, A.B.; Mhaisen, F.T. (Mesopotamian Journal of Marine Sciences, 2022)
Two widely distributed and economically important food fish in the Red Sea were investigated. A total of 101 specimens of Epinephelus tauvina and 120 Abalistes stellatus were collected from Al-Mehwat local fish market, Hodeidah City, Yemen, between October 2009 and April 2010 and examined for their parasites. Two digenean species of the suborder Hemiurata, namely Derogenes varicus (Müller, 1784) and Dinurus scombri Yamaguti, 1934, were found in these fishes. The former parasite occurred in 15% of A. stellatus and 4% of E. tauvina and its mean intensity of infection was 4.2 and 3.5, respectively while the abundance was 15 and 4, respectively. The latter parasite occurred only in 1% of E. tauvina, with a mean intensity of 2 and an abundance of 0.02. The present study represents the first record of these two parasite species in Yemeni waters of the Red Sea. In addition, E. tauvina now represents a new host for D. scombri.